Pole Vault Biomechanics Figures - Angulo-Barroso, R. M.; Kinzler, S. (1993)
The figures listed below are taken from these publications: Angulo-Kinzler, R M, Kinzler, S B, Balius, X, Turro, C, Caubet, J M, Escoda, J and Prat, J A (1993) Biomechanical Analysis of the Pole Vault Event. Scientific report to the International Olympic Committee Medical Commission, Summer Olympic Games of Barcelona 1992, Sant Cugat del Valles: Centre d'Alt Rendiment. Angulo-Kinzler, R M, Kinzler, S B, Balius, X, Turro, C, Caubet, J M, Escoda, J and Prat, J A (1994) Biomechanical Analysis of the Pole Vault Event. Journal of Applied Biomechanics, Vol 10, num 2, pp 147-165, Champaign: Human Kinetics. They illustrate various biomechanical aspects of pole vaulting and were generated from data digitized from videotaped performances at the Summer Olympic Games of Barcelona 1992 by the ABAT project. Cover page Fig. 1.1. Pole Vault Performance History Fig. 3.1. Pole vault phases and events Fig. 3.2. Height ranges Fig. 3.3. Off-center pole force vector Fig. 3.4a. Forces of the vaulter on the pole via the hands Fig. 3.4b. Generation of a forward torque Fig. 3.5. Torque generated by the pole on the vaulter during the pole support phase